Osteopetrosis in a Domestic Shorthair Cat - Beishuizen, Rick; Caliskan, Nermin; Gröne, Andrea; Boroffka, Susanne A.E.B.; Tryfonidou, Marianna A.; Meij, Björn P. (VCOT Open, 2021)
The purpose of this case report was to describe a cat with generalized bone dysplasia, resembling osteopetrosis and Albers-Schönberg disease in humans. A 1-year-3-month-old, intact male, domestic shorthair cat had a 9-month history of multiple bone fractures without known trauma. Most fractures were treated conservatively and two by osteosynthesis. Bone healing occurred but recurring fractures eventually led to euthanasia. Radiographs, computed tomographic imaging, postmortem analysis and histopathologic examination revealed a generalized increase in bone density and mass with preservation of bone shape, obliteration of the bone marrow cavity and persistence of cartilage and primary trabeculae. Abuse and secondary bone diseases were excluded. History, diagnostic bloodwork, radiographs, computed tomographic imaging and histopathologic examination supported the diagnosis of inherited osteopetrosis and strongly resembled Albers-Schönberg disease in humans. The presence of osteoclasts suggested that the underlying pathology might be found in osteoclast dysfunction, deficient number of osteoclasts, inadequate recruitment of osteoclasts, or other micro environmental changes. In (young) cats that are presented with recurring fractures and the possible suspicion of abuse, inherited osteopetrosis should be considered as a differential diagnosis.
Keywords: cat; osteopetrosis; bone displasia; inherited skeletal deformity; pathologic fracture